Water vapor self-continuum absorption measurements in the 4.0 and 2.1 µm transparency windows. (November 2017) - Richard, L.; Vasilchenko, S.; Mondelain, D.; Ventrillard, I.; Romanini, D.; Campargue, A.
Highlights: Water vapor self-continuum absorption measured by OF-CEAS at 2491 cm −1 and by CRDS at 4435 cm −1 . Measurements are validated using the quadratic pressure dependence of the continuum. Temperature dependence studied near 2491 cm −1 between 23 and 52 °C. Our continuum values are much smaller than previous room temperature FTS values. Significant deviations compared to the MT_CKD 3.0 model. Abstract: In a recent contribution [A. Campargue, S. Kassi, D. Mondelain, S. Vasilchenko, D. Romanini, Accurate laboratory determination of the near infrared water vapor self-continuum: A test of the MT_CKD model. J. Geophys. Res. Atmos., 121, 13, 180–13, 203, doi:10.1002/2016JD025531], we reported accurate water vapor absorption continuum measurements by Cavity Ring-down Spectroscopy (CRDS) and Optical-Feedback-Cavity Enhanced Absorption Spectroscopy (OF-CEAS) at selected spectral points of 4 near infrared transparency windows. In the present work, the self-continuum cross-sections, CS, are determined for two new spectral points. The 2491 cm −1 spectral point in the region of maximum transparency of the 4.0 µm window was measured by OF-CEAS in the 23–52 °C temperature range. The 4435 cm −1 spectral point of the 2.1 µm window was measured by CRDS at room temperature. The self-continuum cross-sections were determined from the pressure squared dependence of the continuum absorption. Comparison to the literature shows a reasonable agreement with 1970 s and 1980 s measurements using a grating spectrograph in the 4.0 µm window and a very good consistency with our previous laser measurements in the 2.1 µm window. For both studied spectral points, our values are much smaller than previous room temperature measurements by Fourier Transform Spectroscopy. Significant deviations (up to about a factor 4) are noted compared to the widely used semi empirical MT_CKD model of the absorption continuum. The measured temperature dependence at 2491 cm −1 is consistent with previous high temperature measurements in the 4.0 µm window and follows an exp( D0 /kT ) law, D0 being the dissociation energy of the water dimer. Graphic abstract: